Identification of Medicinal Chemicals in Herbal Medicine for Shortness of Breath in Cirebon Using Thin-Layer Chromatography Method - Indawati, Iin; Bagus Prayogo, Iqbal; Zamzam, Muh Yani (Jurnal Medisci, 2024)
Herbal medicine is prohibited from adding Medicinal Chemicals (BKO), both isolated and synthetic, by Permenkes No. 007 of 2012 Article 7. However, several previous studies found herbal medicine containing BKO; the addition of BKO is indicated so that products from the manufacturer feel faster and have instant efficacy. However, the addition of BKO to herbal medicine has side effects on the organs of the consumer. In 2014 – 2022, BPOM released 12 herbal products that were proven to contain BKO. This study aims to identify the existence of BKO in shortness-of-breath herbal medicine and to find out what BKO is contained in the herbal medicine. Using the purposive sampling method, this study tested six herbal medicine samples with shortness of breath circulating in Cirebon. The techniques used in the identification were thin-layer chromatography (KLT) with the silent phase of GF 254 silica gel, the motion phase of Chloroform, Methanol, and Aquabidest with a ratio of 2: 7: 1. Spot detection through 254 nm UV light. The controlled solution is the test solution (A), the positive control solution (B), and the comparator raw solution (C). Based on the study's results, 5 out of 6 herbal samples containing BKO, Samples 1 and 3 contained CTM and Ephedrine Hcl. Samples 2, 5, and 6 contained Ephedrine HCl only. Sample 4 does not contain BKO.